FAMILY PERCEPTIONS IN COASTAL WASTE MANAGEMENT IN BAKALA VILLAGE, SOUTH BUNGKU DISTRICT, MOROWALI REGENCY - Lamane, Siti Aisa (Jurnal Penyuluhan Pertanian, 2023)
Bakala Village is one of eight coastal villages that cannot be separated from the waste problem. Limited amount of land available for waste management, the absence of officials handling waste management, limited access to sea transportation, the culture of throwing waste on the beach also exists in the community, the absence of a waste management agency responsible for the waste management, the absence of fees for the management of waste released by the community, both during the process of transportation, collection, and disposal of waste, and the community cannot yet be involved on its initiative, there are still indications and need advice. It cannot be denied that household participation in waste management significantly impacts the success or failure of waste management. This study analyzes households' perceptions of coastal waste management in Bakala Village. The study was conducted in July 2023 using a survey research method with a quantitative analysis approach. The sample size was 68 household heads. Descriptive and inferential statistical data analysis using Partial Least Square (PLS). The study results show that parental locus of control, distribution of parental roles, and attitude towards waste management influence the household head's perception of managing coastal waste in Bakala Village.